2016
DOI: 10.1002/chem.201600344
|View full text |Cite
|
Sign up to set email alerts
|

Emergent Catalytic Behavior of Self‐Assembled Low Molecular Weight Peptide‐Based Aggregates and Hydrogels

Abstract: We report a series of short peptides possessing the sequence (FE)n or (EF)n and bearing l-proline at their N-terminus that self-assemble into high aspect ratio aggregates and hydrogels. We show that these aggregates are able to catalyze the aldol reaction, whereas non-aggregated analogues are catalytically inactive. We have undertaken an analysis of the results, considering the accessibility of catalytic sites, pKa value shifts, and the presence of hydrophobic pockets. We conclude that the presence of hydropho… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
87
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
8
2

Relationship

2
8

Authors

Journals

citations
Cited by 119 publications
(92 citation statements)
references
References 68 publications
(24 reference statements)
3
87
0
Order By: Relevance
“…The use of peptides has the advantage that the known catalytic activities of amino acid residues in natural enzymes can be incorporated into the artificial construct. Indeed, functioning artificial biocatalysts from self‐assembled peptides have been developed using a range of designs, including α‐helical coiled‐coils, peptide amphiphiles, short β‐sheet forming peptides,,, aromatic peptide amphiphiles, tripeptide assemblies, and bola‐type amphiphiles . These systems typically incorporate one (or more) histidine and/or other residues relevant to catalysis or binding, sometimes including metal ions to assist folding and catalysis.…”
Section: Figurementioning
confidence: 99%
“…The use of peptides has the advantage that the known catalytic activities of amino acid residues in natural enzymes can be incorporated into the artificial construct. Indeed, functioning artificial biocatalysts from self‐assembled peptides have been developed using a range of designs, including α‐helical coiled‐coils, peptide amphiphiles, short β‐sheet forming peptides,,, aromatic peptide amphiphiles, tripeptide assemblies, and bola‐type amphiphiles . These systems typically incorporate one (or more) histidine and/or other residues relevant to catalysis or binding, sometimes including metal ions to assist folding and catalysis.…”
Section: Figurementioning
confidence: 99%
“…18,24,25 Initial studies with amino acid promoted aldol reactions focused on the formation of tetroses. 18,26 Pizzarello and Weber showed the dimerization of glycolaldehyde by a,a-L-disubstituted amino acids led to the formation of L-tetroses in o7% ee. 18 Similar studies by…”
mentioning
confidence: 99%
“…[15][16][17][18][19] Hydrogel networks can address the solubility problem because hydrophobic aromatic compounds oen associate into the nanober network in water and become reactively accessible. 20 For example, the Meijer 21 and Escuder 22 groups have shown that a self-assembled, 1D ber network enhances catalytic activity compared to its non-assembled counterpart. [23][24][25][26][27][28] Most recent examples of hydrogel photocatalysts 29 involve co-assembling of the photocatalysts with gelators, where catalysts and gelators are two separate components.…”
Section: Introductionmentioning
confidence: 99%